MIRERC 048/2025: CONTEXTUAL FACTORS, COMMUNICATION AND FINANCING STRATEGIES ON ADOPTION OF COMMUNITY-LED TOTAL SANITATION IN PASTORAL COMMUNITIES IN MARSABIT, KENYA - Eliud, Grace (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Access to sanitation facilities is an important human right and a critical United Nation’s agenda, yet millions of people globally still lack such a necessity. Open defecation and adoption of low-quality toilets remain a problem particularly in Sub-Saharan African countries, Kenya included, which amplify risk of disease exposure to the population. Despite approaches to end open defecation such as Community-Led Total Sanitation (CLTS), Kenya is among the global hotspots of open defecation. Although success in CLTS activities has been witnessed in different Kenyan contexts, the approach has shown different results in contexts with pastoral communities. The burden of open defecation in such communities is high with negative trends maintained for years. Context-appropriate approaches to behaviour change are required if universal access to sanitation is to be attained by 2030. The study objectives are to: examine the influence of contextual factors on adoption of Community-Led Total Sanitation, establish the moderating influence of financing strategies and the mediating influence of communication strategies on the relationship between contextual factors and adoption of Community-Led Total Sanitation and to examine the joint influence of contextual factors, financing strategies and information communication on adoption of the approach in the selected pastoral areas in Marsabit, Kenya. The study will employ convergent design and will involve collection of both qualitative and quantitative data. Quantitative data will be gathered from a sample of 395 household heads, a sample calculated using Yamane’s formula. The study will be conducted in two purposively selected Sub-Counties in Marsabit County with the highest and lowest open defecation rates for comparison. A proportionate-to-size simple random sampling technique will be used in selection of household heads from each of the selected areas. The data will be gathered using a questionnaire, an interview guide and an observation checklist. Key informant interviews will be conducted among 12 purposively selected informants who will include Public Health Officers, Community Health Officers, CLTS implementers and selected natural leaders. The quantitative data obtained will be analysed in both descriptives and logistic regressions using the Statistical Package for Social Sciences (SPSS) Version 26. Themes will be identified from the interview data and be presented as narratives. Grey literature sources will also be used to complement data presentation. The study will provide an understanding of the dynamics in pastoral contexts that interact to influence CLTS interventions. It will point out aspects in CLTS that may constrain or enable achievement of the desired outcomes and inform strategies for successful adoption of behaviour change approaches in pastoral communities.